SPESIFIC STUDY OF LAND FOR RICE CROPS IN THE VILLAGE PAGAR PUDING SUB-DISTRICT TEBO ULU REGENCY TEBO PROVINCE JAMBI - Sari Nopi, Rahmat; Hermon, MP, Dr. Dedi; Thesiwati, SP., M.Si, Aslan Sari (STKIP PGRI Sumbar, 2014)
AbstractThis research is conducted with a purpose to 1) Knowing appropriate farm characteristics for the crop of rice field paddy 2) Knowing set of which farm appropriate for the crop of rice fiel paddy in Countryside Pagar Puding District Of Tebo Ulu Sub-Province of Tebo Provinsi Jambi. Set of farm exist in research area consist of 14 set of and farm of sampel research taken only 3 set of farm. Technique intake of sample by using technique of sample regional relied on variation set of farm. Intake of sample by chosening variation set of existing farm purposive sample where taken sample counted one sampel deputizing each;every variation set of farm fulfilling criterion to be made by farm for the crop of rice field paddy. Reason of intake of this method because set of farm which is same to be assumedhave owned is same characteristic also, so that set of the is same farm form can deputize by set of farm. Data analysis the used is descriptive that is analysis in the form of tables of comparison between farm characteristic ( tekstur, structure, permeability, drainage, land;ground pH, organic materials, rainfall, bevel) compared to storey;level according to rice field paddy crop farm. Result of research of that 1) There are difference of farm characteristic that is permeability at one farm, pH in each set of farm, drainage two farm, and organic materials at one farm exist in Countryside Pagar Puding District Of Tebo Ulu Sub-Province of Tebo Provinsi Jambi 2) There are him kinds of according to farm for the crop of rice field paddy in Countryside Pagar Puding District Of Tebo Ulu Sub-Province of Tebo. Set of farm which including category According to ( 2) there are [at] set of fluvial farm form ( F) with farm form of F1. I. Sw. Qa. Lat and set of natural and farm form ( F3) with set of farm of F3.III.Sw.Qtk. Pod, and set of very farm according to ( 1) there are set of plain farm of fluvial ( F3) with set of farm of F1. I. Sw. Qtk. Pod.